Kecanduan Game Online pada Remaja: Dampak dan Pencegahannya - Eryzal Novrialdy (Faculty of Psychology Universitas Gadjah Mada, 2019)
The problem of online game addiction demands public attention. Currently, many studies tend to be focused on efforts to reduce the level of addiction. However, there are very limited studies centered on discussing efforts to prevent this occurrence. This paper aims to examine various alternatives, in order to prevent this form of addiction, especially in adolescents that tend to be the most affected age group. In addition, there have been reports of its impact on several aspects of life, including health, psychologically, academically, socially and financially. Therefore, there is a need for preventive approaches, due to the impacts that disrupt the life of adolescents, which this paper is expected to identify. Furthermore, future research ought to focus on in-depth examination of other alternatives to prevent online game addiction.